Characterization of an equal channel angular pressed Al-Zn-In alloy - C. Banjongprasert (2018)
Equal channel angular pressing (ECAP) is a technique that creates a high accumulated strain in metals and results in ultrafine-grained structure. In this study, Al-5Zn-0.02In was processed by ECAP at a room temperature using route Bc through an ECAP die (press angle of Φ = 100° and Ψ = 20°). The samples were subjected to ECAP with 1, 2, 3 and 4 passes. The processed specimens were characterized using electron backscatter diffraction (EBSD). The results confirmed the grain refinement of the alloy after ECAP to an average grain size less than 5 μm after 4-pass ECAP. The microhardness test shows that the hardness increased with the number of passes. The hardness of the cross-sectional area of the sample was similar to that tested along the pressing direction.